Spin glass like transition and the exchange bias effect in Co3O4 nanoparticles anchored onto graphene sheets. Issue 1 (6th December 2018) - Sarkar, S.; Mondal, A.; Giri, N.; Ray, R.
Abstract : The exchange bias effect is observed in a diluted magnetic system synthesized with 5% volume fraction of Co3 O4 anchored on reduced graphene oxide (rGO) sheet below the antiferromagnetic transition temperature of Co3 O4 . The glassy magnetic phase below 5 K has been established by relaxation memory studies performed in ZFC protocol. Abstract : We have synthesized Co3 O4 nanoparticles having 40 nm average size, which are anchored on reduced graphene oxide. X-ray diffraction, FESEM, TEM and Raman spectroscopy are performed for the characterization. The temperature dependence of field cooled (FC) and zero field cooled (ZFC) magnetization curves exhibits antiferromagnetic (AFM) transition around ∼30 K, as observed for bulk Co3 O4 . The exchange bias effect is observed below ∼30 K. A significant change in the exchange bias effect is noted around ∼8 K, which is close to a spin-glass-like transition. The spin-glass-like phase has been confirmed by the memory effects observed by different experimental protocols. The possible origin of exchange bias is discussed in the manuscript.